Electron energy-loss spectroscopy of single nanocrystals: mapping of tin allotropes. (28th March 2018) - Roesgaard, Søren; Ramasse, Quentin; Chevallier, Jacques; Fyhn, Mogens; Julsgaard, Brian
Abstract: Using monochromated electron energy-loss spectroscopy (EELS), we are able to map different allotropes in Sn-nanocrystals embedded in Si. It is demonstrated that α -Sn and β -Sn, as well as an interface related plasmon, can be distinguished in embedded Sn-nanostructures. The EELS data is interpreted by standard non-negative matrix factorization followed by a manual Lorentzian decomposition. The decomposition allows for a more physical understanding of the EELS mapping without reducing the level of information. Extending the analysis from a reference system to smaller nanocrystals demonstrates that allotrope determination in nanoscale systems down below 5 nm is possible. Such local information proves the use of monochromated EELS mapping as a powerful technique to study nanoscale systems. This possibility enables investigation of small nanostructures that cannot be investigated through other means, allowing for a better understanding and thus leading to realizations that can result in nanomaterials with improved properties.